Paleomagnetism of the Et-Then Group and Mackenzie Diabase in the Great Slave Lake Area - Irving, E.; Park, J. K.; McGlynn, J. C. (Canadian Journal of Earth Sciences, 1972)
Studies of baked contact rocks and material at distances up to several kilometers from contacts show that the Mackenzie diabase acquired its remanent magnetization at the time it originally cooled about 1250 m.y. ago. Baked rocks have coercivities that are generally over twice as high as those of the diabase itself showing that they are suitable for paleomagnettc determinations. Combination of this new data (10 sites) with previous data from the Mackenzie Igneous Episode (Muskox Intrusion, Coppermine lavas, Mackenzie diabase) gives a mean pole position of 01 °N, 171 °W, Red beds of the Et-Then Group are shown to have acquired their magnetization prior to the intrusion of the diabase and probably at the time or soon after they were deposited. They have a mean direction of 294, −21 (k = 17, α 95 = 10°) and a pole at 01 °S, 048 °W (K = 26, A 95 = 8°). The result is based on 14 sites (10 normal 4 reversed).